In situ transformation of Fe-doped Ni12P5 into low-crystallized NiFe2O4 with high-spin Fe4+ for efficient electrocatalytic water oxidation. Issue 16 (13th April 2021) - Wang, Haojie; Zhao, Cuijiao; Wang, Guozhong; Zhang, Haimin
Abstract : Ultrafine Fe-doped Ni12 P5 nanoparticles anchored on cotton-derived P-doped porous carbon were synthesized, exhibiting excellent OER activity, owing to the in situ transformation of Fe-doped Ni12 P5 into low-crystallized NiFe2 O4 with high-spin Fe 4+ . Abstract : The widespread application of renewable energy technologies, such as electrochemical water splitting to produce H2 and rechargeable metal–air batteries, has called for the development of inexpensive and robust oxygen evolution reaction (OER) electrocatalysts. In this work, we report the synthesis of ultrafine Fe-doped Ni12 P5 nanoparticles anchored on cotton-derived P-doped porous carbon ((Fe x Ni y )12 P5 @PPC) by a facile impregnation-pyrolysis process. The results demonstrated that the Fe doping amount in Ni12 P5 plays an important role in regulating the OER activity of electrocatalysts. As a result, the obtained (Fe0.25 Ni0.75 )12 P5 @PPC with a large surface area of 847.2 m 2 g −1 and an average nanoparticle size of ∼8.5 nm exhibited superior OER activity, achieving extremely low overpotentials of 131 and 198 mV at 10 and 100 mA cm −2 in 1.0 M KOH electrolyte, respectively. The comprehensive investigations revealed that low-crystallized NiFe2 O4 with high-spin Fe species in situ transformed from Fe-doped Ni12 P5 during electrocatalysis is responsible for the high OER activity. The findings in this work would be helpful for rational design and development of inexpensive and robust OER electrocatalysts for applications in renewable energy technologies.